Attractiveness of the facial profile: comparison of Class II patients treated with Twin Force® or intermaxillary elastics - Otávio Augusto POZZA; Rodrigo Hermont CANÇADO; Fabricio Pinelli VALARELLI; Karina Maria Salvatore FREITAS; Renata Cristina OLIVEIRA; Ricardo Cesar Gobbi de OLIVEIRA (Dental Press Editora, 2021)
ABSTRACT Objective: To compare the facial profile attractiveness of Class II patients treated with Twin Force® or intermaxillary elastics. Methods: Sample comprised 47 Class II patients divided into two groups: G1) TWIN FORCE - 25 patients treated with fixed appliances and Twin Force® fixed functional appliance (mean initial age was 17.91 ± 7.13 years, mean final age was 20.45 ± 7.18 years, and mean treatment time was 2.53 ± 0.83 years); G2) ELASTICS - 22 patients treated with fixed appliances and Class II intermaxillary elastics (mean initial age was 15.87 ± 5.64 years, mean final age was 18.63 ± 5.79 years and mean treatment time was 2.75 ± 0.60 years). Lateral cephalograms from pretreatment and posttreatment were used. Cephalometric variables were measured and silhouettes of facial profile were constructed and evaluated by 48 laypeople and 63 orthodontists, rating the attractiveness from 0 (most unattractive profile) to 10 (most attractive profile). Intergroup comparisons were performed with Mann-Whitney and independent t-tests. Results: At pretreatment, facial profile of the Twin Force® group was less attractive than the Elastics group. Treatment with Twin Force® or Class II elastics resulted in similar facial profile attractiveness, but the facial convexity was more reduced in the Twin Force® group. Orthodontists were more critical than laypeople. Conclusions: Treatment with Twin Force® or Class II elastics produced similar facial profile attractiveness at posttreatment. Profile attractiveness was reduced with treatment in the elastic group, and improved in the Twin Force® group. Facial convexity was more reduced with treatment in the Twin Force® group.